A case of SARS‐CoV‐2 pneumonia with successful antiviral therapy in a 77‐year‐old man with a heart transplant. Issue 7 (11th June 2020) - Mathies, Daniel; Rauschning, Dominic; Wagner, Ulrike; Mueller, Frank; Maibaum, Maja; Binnemann, Christin; Waldeck, Stephan; Thinnes, Katrin; Braun, Michael; Schmidbauer, Willi; Hagen, Ralf M.; Bickel, Christoph
Abstract : The SARS‐CoV‐2 infection can be seen as a single disease, but it also affects patients with relevant comorbidities who may have an increased risk of a severe course of infection. In this report, we present a 77‐year‐old patient with a heart transplant receiving relevant immunosuppressive therapy who tested positive for SARS‐CoV‐2 after several days of dyspnea, dry cough, and light general symptoms. Computed tomography confirmed interstitial pneumonia. The patient received antiviral therapy with hydroxychloroquine and showed no further deterioration of the clinical state. After 12 days of hospitalization, the patient was released; he was SARS‐CoV‐2 negative and completely asymptomatic. Abstract : This is a report about a patient with heart transplant and SARS‐CoV‐2‐pneumonia who was treated successfully with hydroxychloroquine in consideration of his immunosuppressive comedication.